Effectiveness of Maitland Techniques in Idiopathic Shoulder Adhesive Capsulitis. (24th October 2012) - Kumar, Abhay; Kumar, Suraj; Aggarwal, Anoop; Kumar, Ratnesh; Das, Pooja Ghosh
Abstract : Objective . To study the effectiveness of Maitland techniques in the treatment of idiopathic shoulder adhesive capsulitis. Methods . total of 40 patients diagnosed with idiopathic shoulder adhesive capsulitis were recruited and randomly allocated into two groups. In Group A (n = 20 ) subjects were treated with Maitland mobilization technique and common supervised exercises, whereas subjects in Group B (n = 20 ) only received common supervised exercises. Variables . Shoulder pain and disability index (SPADI), VAS and shoulder ROM (external rotation and abduction) were variables of the study. These were recorded before and after the session of the training. Total duration of the study was four weeks. Result . Statistical analysis of the data revealed that within-group comparison both groups showed significant improvement for all the parameters, whereas between-group comparison revealed higher improvement in Group A compared to the Group B. Conclusion . The study confirmed that addition of the Maitland mobilization technique with the combination of exercises have proved their efficacy in relieving pain and improving R.O.M. and shoulder function and hence should form a part of the treatment plan.